Variabilitas Suhu Permukaan Laut Dan Implikasinya Terhadap Hasil Tangkapan Ikan Cakalang (Katsuwonus pelamis L) Di Perairan Manokwari, Papua Barat - Ridwan Sala; Jafry F. Manuhutu (Jurnal Sumberdaya Akuatik Indopasifik, 2020)
The presence of skipjack fish resources in a fishing area is related to the suitability of the environmental conditions of the waters. This study aims to examine the relationship of sea surface temperature (SPL) to skipjack catches and the characteristics of skipjack catches in Manokwari waters. Data, both catch data and sea surface temperature data, are collected through field surveys by following fishing operations. Furthermore, the data were analyzed descriptively using graphs and mathematically like von Bertalanffy's growth model. The results of this study found that the very small variability of SPL could not explain the variation in the volume of fishermen's catches in Manokwari waters. However, a high SST during the May - August 2013 period is thought to affect the size of the skipjack caught, where the average size of the fish caught inhabited areas near sea level. In addition, the growth of skipjack fish in Manokwari waters is relatively fast with a growth coefficient of 0.42 per year1 and natural mortality between 0.79 per year and 0.81 per year.